DESIGN AND DEVELOPMENT OF CHRONOPHARMACEUTICAL DRUG DELIVERY OF LANSOPRAZOLE - Sandeep, M.; Kishore, V. Sai; Sudheer, B.; Ershad, S.; Adithya, K.; Phanil kumar, D. S (Asian Journal of Pharmaceutical Research and Development, 2013)
The aim of the present investigation is to develop a pulsatile drug delivery system basedon an insoluble capsule body filled with Lansoprazole matrix tablet and sealed with HPMC K 100 plug. The Lansoprazole matrix tablets were prepared by wet granulation method. The plugs of varying thickness and hardness were prepared by direct compression which was then placed in the capsule opening. The drug delivery system was designed to deliver the drug at such a time when it was needed (nocturnal time). Dissolution studies of pulsatile capsule device in media with different pH (1.2, 7.4 and6.8) showed that drug release in colon could be modulated by optimizing the concentration of polymers in the plug and also the position of plug. The study showed that, lag time prior to drugrelease was highly affected by the plug position. The dissolution data revealed that the plug position and the composition of plug were very important to achieve a optimum formulation.Drug– polymer interaction studies indicated no interaction or complexation in between the drug and the polymer.